VARIATION ON WOOD BASIC DENSITY OF Eucalyptus urophylla S.T. BLAKE PROGENIES AT TWO SITES - Mourão Brasil, Maria Aparecida [UNESP]; Arruda Veiga, Ricardo Antonio De [UNESP] (Universidade Federal de Santa Maria, 1994)
The appropriate knowledge about genetic resources potential is essential for the forest patrimony conservation and protection. It is important to emphasize the studies on variation in wood basic density conducted in trials of progenies and provenances. Progenies of Eucalyptus urophylla from Timor Island - Indonesia were planted in Belo Oriente (Minas Gerais state) and Linhares (Espírio Santo state) in the southeastern region of Brazil. The experimented design in three replications was a compact family block with an unequal sub class number at 3.0 x 2.0 m spacings. Four years later, the trees were sampled with increment borer for wood basic density determination at dbh by maximum moisture content method. The results showed that the progenies had a similar behavior at two planting sites. The grater variation among the progenies occurred in Oebaha II region. The progenies density mean values were not different from Brazilian provenances used as control in the experiment.

Estudou-se neste trabalho a variação da densidade básica da madeira entre procedências e progênies de eucalipto plantados em duas localidades. As progênies de Eucalyptus urophylla originárias da Ilha de Timor na Indonésia foram plantadas em Belo Oriente (MG) e Linhares (ES) no delineamento de blocos compactos em famílias (compact family blocks) com 3 repetições no espaçamento de 3,0 x 2,0 m. Após 4 anos as árvores forma amostradas ao nível do DAP com a sonda Pressler e sua densidade básica determinada pelo método do máximo teor de umidade.Os resultado mostraram que as progênies tiveram comportamento similar nos dois locais. A maior variação entre Progênis ocorreu naquelas provenientes da região Oebaha II. Os valores médios de densidade básica das progênies não foram diferentes das procedências brasileiras utilizadas como testemunhas no experimento.
VARIAÇÃO DA DENSIDADE BÁSICA DA MADEIRA DE PROGÊNIES DE Eucalyptus urophylla S.T. BLAKE EM DOIS LOCAIS
Keywords: genetic resources; basic density; progenies; E. urophylla.; recursos genéticos; densidade básica; progênies; E. urophylla.